MUSEUM GEOLOGI DAN PRASEJARAH DI MAKASSAR DENGAN PENDEKATAN ARSITEKTUR HIGH TECH - Saefullah, Saefullah; Muthmainnah, Muthmainnah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Indonesia is rich geological resources consisting of rocks, minerals and minerals. Talking about the geology is very closely related to prehistoric times because of not finding written evidence from prehistoric times, the information concerning this age obtained through fields like paleontology, astronomy, biology, geology, anthropology, and archeology importance of preserving and maintaining prehistoric relics. So will foster a sense of responsibility to it. This is in line with the duties of the Directorate General of Culture Ministry of Education and Indonesian culture in its performance report which suggested that the remains of important historical remains preserved as a living lesson for the next generation. The research objective construct a conceptual foundation design of the design of the Museum of Geology and prehistory with high-tech architecture approach, applying double facade system, Ligth Pipe and photovoltaic systems in buildings, applying intelligent systems in utility buildings. This report is the result of designing buildings and prehistoric geological museum in Makassar with high-tech architecture approach.